From the safety net to the injury prevention web: applying systems thinking to unravel injury prevention challenges and opportunities in Cirque du Soleil - Evert Verhagen; Caroline Bolling; Jay Mellette; H Roeline Pasman; Willem van Mechelen (BMJ Open Sport & Exercise Medicine)
Objective We undertook this qualitative study within an international circus company—Cirque du Soleil—to explore the narrative of artists and the artistic team in regards to injuries and their prevention and to describe the prevention of injuries from a systems thinking lens.Methods Focus groups (FG) with artists and semistructured individual interviews with the artistic team were conducted in six selected shows. The structure of the interviews and FGs concerned the themes: ‘injury’, ‘injury-related factors’ and ‘injury prevention’. Data were analysed through comparative data analysis based on Grounded Theory. Concept mapping and systems thinking approaches were used to design a map of participants’ views on how to prevent injuries.Results Injury was mainly described based on performance limitation. The factors mostly mentioned to be related to injury occurrence were physical load factors. Many of these factors were said to be connected and to influence each other. Injury prevention was mapped as a multilevel system, composed by artist-related factors (eg, technique and life style) and extrinsic factors (eg, touring conditions and equipment) that integrate different strategies and stakeholders.Conclusion Our study reinforces the importance of multilevel injury prevention approaches with shared responsibility and open communication among stakeholders.